2019
DOI: 10.1371/journal.pone.0217853
|View full text |Cite
|
Sign up to set email alerts
|

Effective coverage of facility delivery in Bangladesh, Haiti, Malawi, Nepal, Senegal, and Tanzania

Abstract: Background The persistence of preventable maternal and newborn deaths highlights the importance of quality of care as an essential element in coverage interventions. Moving beyond the conventional measurement of crude coverage, we estimated effective coverage of facility delivery by adjusting for facility preparedness to provide delivery services in Bangladesh, Haiti, Malawi, Nepal, Senegal, and Tanzania. Methods The study uses data from Demographic and Health Surveys (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 35 publications
(40 reference statements)
4
61
0
Order By: Relevance
“…Improvements in caesarean section rates were concentrated in urban areas, indicating that rising facility births did not greatly improve access to emergency obstetric and newborn care in rural areas. In line with previous studies finding substantially lower effective than crude coverage of childbirth care,18 52–54 these findings raise important concerns about the quality of care provided to women in Senegalese facilities, and elsewhere in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Improvements in caesarean section rates were concentrated in urban areas, indicating that rising facility births did not greatly improve access to emergency obstetric and newborn care in rural areas. In line with previous studies finding substantially lower effective than crude coverage of childbirth care,18 52–54 these findings raise important concerns about the quality of care provided to women in Senegalese facilities, and elsewhere in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 84%
“…Among sub-Saharan countries with Demographic and Health Survey (DHS) data, Senegal has the highest percentage of women delivering in facilities who report no skilled attendant (19% in 2014),9 34 and the deficit of midwives was estimated at 50% of the need in 2013 32 35. Low availability of anticonvulsants for hypertensive disorders, manual vacuum extractors and provider CEmONC training have been highlighted as gaps in EmONC readiness 36…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2018 literature review [5] found that of six papers that combined population and health facility data sources, four did not report an estimate of the variance of the point estimate [11,12,15,16]; one used the exact method for the product of two variables [17], and the sixth used a Taylor series expansion [19]. Recently published work on the effective coverage of childbirth defined and employed the delta method for variance calculation [23,24].…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%
“…We describe three methods for constructing a 95% confidence interval around an effective coverage estimate: two analytical approaches, the exact and the delta methods, and a computer-based approach, the bootstrap method, which involves repeated sampling with parameters estimated from the observed data. The derivation for confidence interval construction using the delta method was presented previously in Wang et al [23,26].…”
Section: Calculating a Confidence Interval For Effective Coveragementioning
confidence: 99%